Analisis Pengaruh Faktor Fundamental Terhadap Harga Saham dengan Return on Asset Sebagai Variabel Intervening Pada Perusahaan Manufaktur Sektor Industri Dasar & Kimia Bursa Efek Indonesia Periode 2018-2021 - Harianja, Theresia Shintia; Hafas, Hafriz Rifki; Setiamy, Arasy Ayu (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Stock trading in the capital market is a very important aspect of the economy of Indonesia and other countries. This study aims to determine : (1) The Effect of Debt to Assets Ratio (DAR), Working Capital to Total Assets (WC/TA), Current Ratio (CR), to Return On Assets (ROA), (2) The Effect of Debt to Assets Ratio (DAR), Working Capital to Total Assets (WC/TA), Current Ratio (CR), and Return On Assets (ROA) to Stock Price, (3) The Effect to Debt to Assets Ratio (DAR), Working Capital to Total Assets, and Current Ratio (CR) to the Stock Price through Return On Assets (ROA) as an Intervening Variable. The research samples are companies that included in The Sector Industry basic and chemicall in the period 2018-2021 by using Purposive Sampling method. There are 17 companies that meet the criteria as the sample. This research used path analysis which is the development of multiple regression analysis and bivariate. The result of this research showed that: DAR has a negative and significant effect on ROA, WCTA has a positive and significant effect on ROA, CR has a positive and insignificant effect on ROA, DAR has a negative and insignificant effect on stock prices, WCTA has a positive and significant effect on stock prices. CR has a positive and significant effect on share prices, ROA has a negative and significant effect on share prices. The results of the Sobel test show that DAR, WCTA, ROA have an Indirect Effect.